Primula chongqingensis (Primulaceae), a new species from Chongqing, China - Liang, Ke (Jungle); Zhang, Hong-Jing; Yi, Si-Rong (Phytotaxa, 2026)
Primula chongqingensis K.Liang & S.R.Yi, sp. nov., a new species of Primula sect. Ranunculoides from Chongqing, China, is described. The new species is currently known only from Qianjiang District, where it grows on wet moss-covered rock faces and dripping cliffs beside streams and below waterfalls in shaded valley woodland. It is most similar to P. ranunculoides in overall morphology, but differs by its smaller leaves with markedly fewer lateral segments, stable long-homostylous flowers, pedicels and calyces covered with short glandular hairs, and a relatively short calyx less than half as long as the corolla tube, usually reaching ca. one third of it. Filiform propagative shoots with apical bulblets are only occasionally produced in P. chongqingensis, whereas similar structures are consistently and abundantly produced in P. ranunculoides. These combined vegetative and reproductive differences support its recognition as a distinct species rather than an infraspecific taxon of P. ranunculoides. A morphological description, distribution information, provisional conservation assessment, a diagnostic comparison with P. ranunculoides, and a key to the species of Primula sect. Ranunculoides are provided.